A STUDY ON CUSTOMER RELATIONSHIP MANAGEMENT IN CONSUMER MARKETS: GRANDIOSITY/ REALITY? - Ashish GUPTA (Management & Marketing)
Relationship marketing (RM) was conceived as an approach to industrial and service markets, and was considered inappropriate in other marketing contexts. Recently, however, the domain of RM has been extended to incorporate innovative applications in mass consumer markets. Much has changed in a few short years. Recent applications of RM in consumer markets have been facilitated by developments in direct and database marketing within an increasingly competitive and fragmented marketplace. This paper presents a critical review of the history of RM in consumer markets, and incorporates important conceptual, practical, empirical and popular contributions. A number of critical issues which remain unresolved are identified in the paper. These form the basis of ten research propositions which are crucial to justifying and advancing the domain extension into consumer markets.